Hedging the Purchase: Integrating Financial Risk into the Webrooming Journey (Journal of Asian Development Studies, 2026)
In this study, the authors analyse the effects of smart shopping perception, salesperson assistance, and socialisation on webrooming behaviour, with financial risk as a moderating factor. PLS-SEM is used to analyse the data and shows that these variables have a significant effect on webrooming behaviour. Physical stores can provide in-store expert advice and foster a positive atmosphere for customers to interact with one another, motivating them to visit physical stores at the time of purchase. Furthermore,customers with a higher financial risk perception are more likely to exhibit webrooming than those with a lower one. Online companies can minimise the financial risk associated with online purchases, retain customers in a single channel –online –and prevent them from switching at the time of purchase.